2010
DOI: 10.1111/j.1365-2125.2010.03654.x
|View full text |Cite
|
Sign up to set email alerts
|

Oversight: a retrospective study of biochemical monitoring in patients beginning antihypertensive drug treatment in primary care

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Guidelines recommend biochemical monitoring of patients treated with antihypertensive agents, although there is little primary evidence for these recommendations. WHAT THIS STUDY ADDS • Patients treated for hypertension in general practice often have no biochemical tests before, or in the 6 months after, starting drug treatment. AIMS Guidelines on the management of hypertension have recommended baseline testing of serum electrolyte and creatinine concentrations bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
3
8
0
Order By: Relevance
“…26 30 Consistent with some,26 30 but not all, previous studies,28 we found no association for diabetes. However, these previous studies reporting an association for diabetes focused on monitoring within broader intervals ( eg, 6 months),28 where patients with diabetes, irrespective of ACEI/ARB initiation, were likely to receive blood testing owing to the diabetes QOF programme.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…26 30 Consistent with some,26 30 but not all, previous studies,28 we found no association for diabetes. However, these previous studies reporting an association for diabetes focused on monitoring within broader intervals ( eg, 6 months),28 where patients with diabetes, irrespective of ACEI/ARB initiation, were likely to receive blood testing owing to the diabetes QOF programme.…”
Section: Discussionsupporting
confidence: 91%
“…Only one previous study19 examined monitoring according to guideline-recommended intervals (<14 days). All others have used longer intervals ( eg, 30 days26 or 6 months27 28), which make interpretations and implications for clinical practice less clear. Poor adherence to monitoring guidelines after ACEI/ARB initiation is not restricted to the UK,19 28 29 but has also been reported in the USA,30–32 Canada33 and the Netherlands 26…”
Section: Discussionmentioning
confidence: 99%
“…The comprehensive list of indications for this pharmaceutical category illustrates how frequently these drugs are used in daily medical practice. 8,9 Worldwide heparin utilization trends have shown 10% to 15% yearly growth in the past decade. These medicines were primarily used in the inpatient setting, and heparins consumed up to 10% of the total medication costs in hospitals.…”
Section: Safety Assessmentsmentioning
confidence: 99%
“…In the more general population the benefits of diagnostic test monitoring are not known with confidence, and it occupies a great deal of resources in practice [29], but further research in this area is also required.…”
Section: Priority 5: a Research Priority Is To Describe Adverse Reactmentioning
confidence: 99%